YES/NO AS DOMINANTS OF THE TOLERANT SET CONSENT/ NON-CONSENT IN RUSSIAN. - MATEVOSYAN, LIANNA (Bulletin of Yerevan University H: Russian Philology, 2020)
The paper deals with stereotypical utterances,Yes and No, regarded as dominants of the tolerant set Consent/Non-consent.Members of the tolerant set are close or identical in meaning but different in expression,and they are not always interchangeable. The latter provokes errors in the speech ofnon-native speakers of Russian, which makes it critically important to study and teach Russian as a foreign language.
Keywords: utterances, yes, no, synonymy, tolerant set, consent, non-consent